Determinants of Uromodulin Levels among Patients with Type 2 Diabetes Mellitus - Muntadher Al Bahhash; Abrar I. Albadr; Abdulhussein Aljanabi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Uromodulin, a kidney-specific glycoprotein, is associated with renal function and is frequently reduced in diabetes and chronic kidney disease. Specific Background: In type 2 diabetes mellitus, metabolic disturbances contribute to tubular injury, with declining uromodulin levels observed during disease progression. Knowledge Gap: However, the relationships between uromodulin levels and demographic and clinical determinants such as age, gender, body mass index, glycemic control, and duration of diabetes remain insufficiently clarified. Aims: This study aimed to evaluate the association between uromodulin levels and these variables in patients with type 2 diabetes mellitus. Results: A case-control study involving 176 participants demonstrated significant variations in uromodulin levels (p<0.001), with lower concentrations associated with advancing age, higher body mass index, longer duration of diabetes, worsening glycemic control, and increased disease severity, particularly in advanced diabetic nephropathy stages (DN2 and DN3). Females generally exhibited higher uromodulin levels compared to males. Novelty: This study provides integrated evidence linking multiple demographic and metabolic determinants with uromodulin variation across different stages of diabetic kidney disease. Implications: The findings suggest that reduced uromodulin levels may serve as a biomarker for disease progression and risk stratification, supporting its potential utility in clinical monitoring and early identification of high-risk patients with type 2 diabetes mellitus. Highlights:• Uromodulin levels decline progressively across advanced diabetic nephropathy stages• Demographic and metabolic factors show significant associations with biomarker variation• Lower concentrations observed in prolonged disease duration and poor glycemic status Keywords: Uromodulin, Type 2 Diabetes Mellitus, Diabetic Kidney Disease, Glycemic Control, Body Mass Index